1989
DOI: 10.1111/j.1348-0421.1989.tb01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Fiber on Human Fecal Microflora

Abstract: The effects of brown rice, containing fourfold as much dietary fiber as polished rice, on the human fecal microflora were determined. Significantly increased numbers of Bifidobacterium adolescentis and Enterococcus faecalis were observed during the brown rice intake, whereas the total counts and the numbers of bacteroides, Eubacterium aerofaciens, and Escherichia coli during the intake were lower than those before and after the intake. Lower numbers of clostridia and low incidences of Clostridium paraputrificu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…Conversely, Fuchs et al (12) noted a significant increase in the number of total anaerobes, and higher numbers of clostridia and streptococci when volunteers were given a high fiber diet, while the numbers of eubacteria and lactobacilli decreased. Benno et al (1) demonstrated that a high fiber intake causes changes in microbial populations; significantly higher numbers of Bifidobacterium adolescentis and Enterococcus faecalis and significantly lower numbers of bacteroides, eubacteria, and clostridia were observed. In the present study, the numbers of lecithinase-negative clostridia in the feces decreased significantly (P<0.01) during the HCP diet compared to LC or HC diets.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Fuchs et al (12) noted a significant increase in the number of total anaerobes, and higher numbers of clostridia and streptococci when volunteers were given a high fiber diet, while the numbers of eubacteria and lactobacilli decreased. Benno et al (1) demonstrated that a high fiber intake causes changes in microbial populations; significantly higher numbers of Bifidobacterium adolescentis and Enterococcus faecalis and significantly lower numbers of bacteroides, eubacteria, and clostridia were observed. In the present study, the numbers of lecithinase-negative clostridia in the feces decreased significantly (P<0.01) during the HCP diet compared to LC or HC diets.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal nutritional conditions resulting from an oversupply of soluble carbohydrate can, however, lead to runaway production of lactate in the rumen, leading to the serious condition lactic acidosis (48). Although Megasphaera and Veillonella-related organisms have been reported from the human GI tract (5,19), molecular studies indicate that their populations may be quite variable between individuals (24,27,49). Meanwhile, recent reports suggest that significant amounts of lactate may be converted into butyrate in the human colonic system (7).…”
mentioning
confidence: 99%
“…To date, the research demonstrates a decrease in Bifidobacterium and an increase in the total number of Enterobacteriaceae [44,45] (Tables 4 and 5).…”
Section: Changes In the Microflora With Agingmentioning
confidence: 95%